2010
DOI: 10.1177/194008291000300305
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Reintroduced Tigers in Sariska Tiger Reserve, Western India: Preliminary Findings on Home Range, Prey Selection and Food Habits

Abstract: ). Tigers fed on seven prey species as shown by kill data. Tigers' scat analysis revealed the presence of five prey species. Prey selection by tigers based on scat analysis was in the following order: sambar> chital> nilgai> livestock> common langur. It is proposed to restock the tiger population initially with five tigers in Sariska and subsequent supplementation of two tigers every three years for a period of six years, which will allow the population to achieve demographic viability. Removal of anthropogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…So, the increased prey density may indeed be able to support large carnivore population of the park. These results are comparable with other sites of the Indian subcontinent (Sankar et al, 2010). Sariska Tiger Reserve harbors relatively high density of wild prey species, than Nagarhole and other south Asian sites given in the Table 3.…”
Section: Comparison Of Population Densitysupporting
confidence: 78%
“…So, the increased prey density may indeed be able to support large carnivore population of the park. These results are comparable with other sites of the Indian subcontinent (Sankar et al, 2010). Sariska Tiger Reserve harbors relatively high density of wild prey species, than Nagarhole and other south Asian sites given in the Table 3.…”
Section: Comparison Of Population Densitysupporting
confidence: 78%
“…After the tiger extermination in Sariska, leopard took over the entire tiger habitat (Sariska National Park), which was the best habitat available in Sariska and became the top predator (Sankar et al 2009). Afterwards, the re-introduced tigers again established their territory in the same area of Sariska National Park (Sankar et al 2010). Several hypotheses have been proposed to explain the prey selection by competitor predators.…”
Section: Introductionmentioning
confidence: 99%
“…After the relocation of tigers, the habitat situation has been improved in Sariska but many threats still exist (Sankar et al 2010). It has already been reported that biomass extraction is leading to the changes in vegetation composition of the reserve (Kumar & Shahabuddin 2005;Gupta & Yadav 2005;Yadav & Gupta 2006, 2007 and it is changing the bird composition also.…”
Section: Discussionmentioning
confidence: 99%
“…These areas can be considered highly conserved core blocks for birds. Sankar et al (2010) also suggested the same areas for the conservation of the tiger. Many threatened bird species have been sighted in these areas only (Appendix 1).…”
Section: Discussionmentioning
confidence: 99%